Injury patterns in elite german soccer players: injury history, typologies, and implications - Schwiete, C.; Broich, H.; Mester, J.; Wigger, U.; Behringer, M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Injuries & infections in soccer are commonly associated with prolonged periods of downtime for players as well as financial costs for clubs. However, the origin and time period of downtime can vary greatly. Among others, muscle injuries have been reported to be a major reason for absence in soccer players. The aim of the present study was to compile the injuries of an elite German soccer club to see if different injury patterns regarding the affected structures can be identified. METHODS: Total injuries of 49 first league german soccer players (23.6 ± 4.4 years) were collected and analyzed over the course of 14 consecutive seasons (07/08 - 22/23). All presented data were obtained from a publicly accessible database (transfermarkt.de). Injuries were categorized regarding their type (muscle, infect, joint, tendon/ligament, back, others), and days of absence were screened. RESULTS: In total, 573 injuries occurred, including 183 muscle injuries (31,9%). This accumulated in 13590 days of absence for all players; 2790 days could be attributed to muscle injuries. There was a great variance regarding muscle-related absence, ranging from 0 - 383 total days (mean: 56.5 ± 78.8 days). On average, 16% ± 18.4% of all injuries were muscle-related, with accumulations of up to 65% in individual players. CONCLUSION: The results of this study show that muscle injuries were a major cause of prolonged periods of absence in the tested elite german soccer players. Furthermore, it appears that both the absolute muscle injuries and the relative distribution among players varies greatly and there may be players who are more susceptible to injuries of a muscular origin than others. Knowledge of such individual injury profiles is important to enable physicians and coaches to manage individual loading to minimize the risk of injury and infections.